2007
DOI: 10.1007/s10792-007-9134-x
|View full text |Cite
|
Sign up to set email alerts
|

Causes of childhood visual impairment and unmet low-vision care in blind school students in Ghana

Abstract: The purpose of this study was to determine the causes of childhood visual impairment and blindness in students of a school for blind children, to determine how many students had some residual vision, and to evaluate any unmet low-vision care. A survey of students in the blind school was conducted in two parts in May-June and then October 2003. The sample consisted of 201 students who became blind before the age of 16. Information was obtained from student interviews, doctors' referral notes and ophthalmic exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 9 publications
5
36
0
Order By: Relevance
“…This corroborates findings from studies in schools for the blind in Ghana [3][4][5] and reports from Nigeria [6,7]. The frequency of visual impairment (62%) in our study was comparable with that found in previous studies in schools for the blind in Ghana [4,5].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This corroborates findings from studies in schools for the blind in Ghana [3][4][5] and reports from Nigeria [6,7]. The frequency of visual impairment (62%) in our study was comparable with that found in previous studies in schools for the blind in Ghana [4,5].…”
Section: Discussionsupporting
confidence: 92%
“…This corroborates findings from studies in schools for the blind in Ghana [3][4][5] and reports from Nigeria [6,7]. The frequency of visual impairment (62%) in our study was comparable with that found in previous studies in schools for the blind in Ghana [4,5]. It is possible that some infants would have been categorized as having visual impairment had there been a quantitative assessment of acuity, and this would have increased the frequency of visual impairment in our population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the study from west of Scotland, some of the students with blindness also had co-existing multiple disabilities [18]. Corneal scarring still remains the most common cause of childhood blindness in sub-Saharan Africa [3,19]. Visual impairment was caused by refractive error and cataract among 7 students with hearing disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Services for the blind children in developing countries need to be improved (Pal et al, 2006;Ntim-Amponsah and Amoaku, 2008;Okoye et al, 2009). In addition, a need was expressed to involve blind volunteer teachers as they would be better able to understand the problems that blind children face than professionally-trained sighted teachers.…”
Section: Discussionmentioning
confidence: 99%